MENINGKATKAN PRESTASI BELAJAR MELALUI PENERAPAN STRATEGI PEMBELAJARAN KOLABORASI PADA MATA PELAJARAN PKn - Marmiati - (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2015)
This research was exposed by low level of student learning results on subjects PKn grade V at SDN Mungkung 2, Loceret, Nganjuk, lessons learned from the results of the observation. The purpose of this research is to improve the learning results of the implementation of the strategy by using the PKn collaboration. This research are a class action research cycle is a recurring cycle. Each cycle is implemented through 4 stages of planning, implementation, observation, and reflection. Data collection was done through observation and tests, by using a sheet of observations as well as the test questions were analyzed using quantitative and qualitative analysis techniques. The subject of this research is on grade V totalling 28 people. Data collection techniques used to measure learning outcomes students use quantitative data that is written and test to measure the activity of the teacher in the classroom used qualitative data i.e. observation sheets.The results of this research show that collaborative learning strategies have a positive impact in improving the learning achievements of students in the class of Pkn V SDN Mungkung 2 Kecamatan Loceret Nganjuk. It can be seen from the increase in mastery learning students in every cycle is the first cycle of students learning completeness percentage of 58.89% increased in the second cycle into 77.71% and completed in the target category of learning in the classroom. KEYWORDS: study achievement, pkn, colaboration learning strategy